2020
DOI: 10.1002/cam4.3269
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban thromboprophylaxis in ambulatory patients with pancreatic cancer: Results from a pre‐specified subgroup analysis of the randomized CASSINI study

Abstract: Background Pancreatic cancer patients are at risk for venous thromboembolism (VTE); the value of thromboprophylaxis has not been definitively established. Methods This trial randomized cancer patients initiating a new regimen and at high risk for VTE (Khorana score ≥2) to rivaroxaban 10 mg or placebo up to day 180. This analysis examined the subset of pancreatic cancer patients. The primary efficacy endpoint was the composite of symptomatic deep‐vein thrombosis (DVT), asymptomatic proximal DVT, any pulmonary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…A total of 2156 records were identified through database searching. After title and abstract screening, 6 studies were assessed for eligibility [25,26,[29][30][31][32][33]. One study did not report data separately from the subgroup of PC patients [33].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 2156 records were identified through database searching. After title and abstract screening, 6 studies were assessed for eligibility [25,26,[29][30][31][32][33]. One study did not report data separately from the subgroup of PC patients [33].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…One study did not report data separately from the subgroup of PC patients [33]. Finally, 5 studies meeting the inclusion criteria were included in the meta-analysis ( Figure S1) [25,26,[29][30][31][32]. The agreement between reviewers for study selection was 100% (kappa statistic 1.0), and no further resolution by a third reviewer was required.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this Special Issue of Cancers , results from a meta-analysis pooling data from 1003 PC patients included in five RCTs comparing pharmacological thromboprophylaxis to placebo or no placebo control for VTE prevention demonstrated that primary thromboprophylaxis decreases the risk of VTE by 69%, without increase in the risk of major bleeding [ 16 ]. This systematic review and meta-analysis included data from a subgroup of PC patients enrolled in a DOAC placebo-controlled trial for primary VTE prevention [ 27 ]. The results support the most recent ITAC [ 5 ] and ASCO [ 6 ] guidelines that recommend primary prophylaxis using either LMWH or DOAC for all ambulatory PC patient receiving systemic anticancer therapy and with a low risk of bleeding.…”
mentioning
confidence: 99%